The Art Project Practice Learning: Early Childhood Education in Children's Fine Motor Development - Dewi Pratiwi; Dwiana Asih Wiranti; Niken Ayu Nila Ariani (Universitas Negeri Semarang, 2023)
Children are dynamic individuals and have the urge to be curious about everything. This research aims to develop children's fine motor skills through Art Project Practice activities at TK Pertiwi Sidorekso, Kudus, Indonesia. The research subjects consist of 7 boys and 10 girls. The Art Project Practice carried out is assembling and coloring the giant APE sub-theme of land transportation equipment. The method used is mixed methods with an exploratory sequential research design. This research was conducted in stages (sequential) where the researcher firstly started by exploring qualitative data and analyzing it then using the findings in the qualitative phase to develop instruments and analyze them quantitatively. While the collecting data applies interviews, observations, documentation and questionnaires. Qualitative data analysis uses data reduction, data presentation and draw conclusions. Meanwhile, the quantitative data were analyzed using descriptive statics. The instrument obtained can be used to measure children's fine motor development. The results showed that Art Project Practice making and coloring giant APE could improve children's fine motor skills by 22%. The indicators of fine motor development assessed were assembling the giant APE pattern, cutting geometric shapes, accuracy in pairing geometric shapes, brush holding strength, and coloring abilities that had reached the expected level of development (BSH). From the responses, it indicates that children prefer to carry out Art Project Practice on the sub-theme of land transportation because learning is conducted according to the character of children's play and the creation of works of art.